The effect of audit team’s emotional intelligence on reduced audit quality behavior in audit firms: Considering the mediating effect of team trust and the moderating effect of knowledge sharing - Zhao, Mingyuan; Li, Yuyue; Lu, Jie (Frontiers in Psychology, 2022)
Reduced audit quality behavior is widespread in the auditor's practice and is an important factor threatening audit quality. Some prior studies have investigated the relationship between auditors’ psychological contract violation and reduced audit quality behavior. However, the research of relationship between emotional intelligence (EI) and auditors’ behavior is still in its infancy despite the fact that the auditing profession would benefit greatly from improving audit team’s EI. This study examines whether and why the audit team's EI restrains the audit quality reduction behavior in audit firms. In the study, our hypotheses are tested using a data set collected from 326 respondents in Chinese audit firms. The results are as follows: Firstly, audit team's EI is directly negatively related to reduced audit quality behavior. Secondly, EI is indirectly related to reduced audit quality behavior, through team trust. The results of structural equation modeling (SEM) indicate a mediation model where team trust is negatively related to reduced audit quality behavior. Thirdly, knowledge sharing is a significant mechanism that moderates the effects of different types of EI on audit quality reduction behavior. In the audit team with high knowledge sharing, the audit team’s EI can refrain the audit quality reduction behavior; In the audit team with low knowledge sharing, the audit team’s EI has no significant effect on audit quality reduction behavior. This study expands the factors affecting audit quality to the psychological level of audit teams, enriches the literature on audit team’s behavior characteristics, and provides direct evidence for the relationship between audit team’s psychological characteristics and audit quality.